A Sufentanil-Based Rapid Cardiac Anesthesia Regimen in Children Undergoing Percutaneous Minimally-Invasive Intraoperative Device Closure of Ventricular Septal Defect - Zeng-Chun Wang (Brazilian Journal of Cardiovascular Surgery)
Abstract Objective: To assess the effectiveness and safety of fast-track cardiac anesthesia using the short-acting opioid sufentanil in children undergoing intraoperative device closure of ventricular septal defect (VSD). Methods: This retrospective clinical study included 65 children who underwent intraoperative device closure of VSD between January 2017 and June 2017. Patients were diagnosed with isolated perimembranous VSD by transthoracic echocardiography. Then, they were divided into two groups, group F (n=30), whose patients were given sufentanil-based fast-track cardiac anesthesia, and group C (n=35), whose patients were given conventional cardiac anesthesia. Perioperative clinical data were analyzed. Results: No significant differences were found between the preoperative clinical parameters and intraoperative hemodynamic indices between the two groups. In group C, compared with group F, the postoperative duration of mechanical ventilation, the length of stay in the intensive care unit, the length of hospital stay, and the hospital costs were significantly increased. Conclusion: In this retrospective study at a single center, sufentanil-based fast-track cardiac anesthesia was shown to be a safe and effective technique for minimally-invasive intraoperative device closure of VSD in children, which was performed with reduced in-hospital costs.